2021
DOI: 10.1038/s41598-021-88224-5
|View full text |Cite
|
Sign up to set email alerts
|

TRPM2 ion channels steer neutrophils towards a source of hydrogen peroxide

Abstract: Neutrophils must navigate accurately towards pathogens in order to destroy invaders and thus defend our bodies against infection. Here we show that hydrogen peroxide, a potent neutrophil chemoattractant, guides chemotaxis by activating calcium-permeable TRPM2 ion channels and generating an intracellular leading-edge calcium “pulse”. The thermal sensitivity of TRPM2 activation means that chemotaxis towards hydrogen peroxide is strongly promoted by small temperature elevations, suggesting that an important funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…MCP1 secreted by endothelial cells in response to subendothelial deposition of oxLDL is one of the initial driving forces of macrophage infiltration during atherosclerosis [112]. Similar to our findings, hydrogen peroxide (H 2 O 2 ) was shown to attract neutrophil migration both in vivo and in intro, which was also abolished by TRPM2 knockout or TRPM2 inhibition [114]. H 2 O 2 is an important molecular signal generated during inflammation [115].…”
Section: Trpm2 In Atherosclerosissupporting
confidence: 84%
“…MCP1 secreted by endothelial cells in response to subendothelial deposition of oxLDL is one of the initial driving forces of macrophage infiltration during atherosclerosis [112]. Similar to our findings, hydrogen peroxide (H 2 O 2 ) was shown to attract neutrophil migration both in vivo and in intro, which was also abolished by TRPM2 knockout or TRPM2 inhibition [114]. H 2 O 2 is an important molecular signal generated during inflammation [115].…”
Section: Trpm2 In Atherosclerosissupporting
confidence: 84%
“…Different reports have shown that these channels can enhance T cell receptor stimulation in T cells and inhibit reactive oxygen species production in phagocytic cells (Di et al, 2011;Chung et al, 2015;Syed Mortadza et al, 2015;Morad et al, 2021). Furthermore, this channel can promote the secretion of cytokines such as IL-2, IL-17, and IFN-γ (Melzer et al, 2012).…”
Section: Calcium Channelsmentioning
confidence: 99%
“…with H 2 O 2 or LPS and at experimental time points (see methods below), mice were euthanised by cervical dislocation. The peritoneal lavage was recovered as above, and samples of the suspensions were immediately spun down onto glass slides using a cytocentrifuge (Sigma 2-7 Cyto, Shandon TM , Germany as described below) and leukocytes (neutrophils, macrophages) identi ed through a fast-acting modi ed version of the May-Grünwald-Giemsa staining and subsequent cell type identi cation as shown in Morad et al 2021. The remaining cell suspension was then centrifuged for 10 min at 200 RCF and supernatants were collected and frozen at -20 o C for cyto/chemokine analysis by ELISA and cf-DNA(NET) quanti cation using Quant-iT™ PicoGreen kit (Thermo Fisher).…”
Section: In Vivo Peritoneal Chemotaxis Experimentsmentioning
confidence: 99%
“…Samples of the BAL uid were immediately spun down onto glass slides using a cytocentrifuge (as described below) and neutrophils identi ed through a fast-acting modi ed version of the May-Grünwald-Giemsa staining and subsequent cell type identi cation as shown in Morad et al 2021. The remaining cell suspensions was then centrifuged for 10 min at 200 RCF and supernatants were collected and frozen at -20°C for cyto/chemokine analysis by ELISA and cf-DNA (NET) quanti cation using Quant-iT™ PicoGreen kit (Thermo Fisher).…”
Section: Isolation Of Mouse Balf Neutrophilsmentioning
confidence: 99%